2012
DOI: 10.1098/rspb.2012.1357
|View full text |Cite
|
Sign up to set email alerts
|

Vampire squid: detritivores in the oxygen minimum zone

Abstract: Vampire squid (Vampyroteuthis infernalis) are considered phylogenetic relics with cephalopod features of both octopods and squids. They lack feeding tentacles, but in addition to their eight arms, they have two retractile filaments, the exact functions of which have puzzled scientists for years. We present the results of investigations on the feeding ecology and behaviour of Vampyroteuthis, which include extensive in situ, deep-sea video recordings from MBARI's remotely operated vehicles (ROVs), laboratory fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 33 publications
2
64
1
3
Order By: Relevance
“…The pelagic realm of modern OMZs is characterized by a diversity of carnivores that, in the cores of OMZs, usually migrate to more oxygenated water to pay off this oxygen debt (42). Interestingly, however, some permanently pelagic OMZ residents such as the vampire squid have adapted to low-oxygen levels by losing the carnivorous feeding habit that is primitive for cephalopods and becoming detritivores (43). The inability to pay off an oxygen debt in the chronically low-oxygen benthos, where organisms are unable to migrate to higher-O 2 waters, represents the most likely explanation for the observation that polychaete carnivore species diversity and percentage of the total fauna correlate with oxygen level.…”
Section: Oxygen and Carnivory In Modern Omzsmentioning
confidence: 99%
“…The pelagic realm of modern OMZs is characterized by a diversity of carnivores that, in the cores of OMZs, usually migrate to more oxygenated water to pay off this oxygen debt (42). Interestingly, however, some permanently pelagic OMZ residents such as the vampire squid have adapted to low-oxygen levels by losing the carnivorous feeding habit that is primitive for cephalopods and becoming detritivores (43). The inability to pay off an oxygen debt in the chronically low-oxygen benthos, where organisms are unable to migrate to higher-O 2 waters, represents the most likely explanation for the observation that polychaete carnivore species diversity and percentage of the total fauna correlate with oxygen level.…”
Section: Oxygen and Carnivory In Modern Omzsmentioning
confidence: 99%
“…Life history theory predicts that iteroparity is favoured when adult survival is increased [10]. With the ability to inhabit low oxygen environments, where predators are fewer [6], vampire squid may benefi t from increased adult survival rates, allowing for multiple reproductive cycles at low reproductive cost. …”
mentioning
confidence: 99%
“…This coleoid cephalopod occurs at open ocean depths between 500 and 3000 m and is able to inhabit low oxygen environments [5]. Vampire squid feed opportunistically on zooplankton and detritus [6]. Young [7] observed that in adult females, developing eggs were present in various sizes (up to 3 mm), "indicating a lack of a development cycle and a lack of a restricted breeding period", but the exact reproductive strategy of vampire squid remained unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations